A Singular Novel--Amaral's 1886 Os habitantes do planeto Saturno [The Inhabitants of the Planet Saturn]. - Bonifácio, Vitor (Science Fiction Studies, 2019)
Os habitantes do planeta Saturno [The Inhabitants of the Planet Saturn] by the mysterious nineteenth-century Portuguese author António Peixoto do Amaral may be the first fully realized work of sf in Portuguese. Published in 1886, it shows a clear debt to Jules Verne's interplanetary voyage extraordinaire, Hector Servadac (1877), but it also includes elements specific to the contemporary Portuguese cultural context such as the promotion of a Catholic conservative political agenda, among others.